Microvascular disease and cardiovascular outcomes among individuals with type 2 diabetes. (June 2021) - Kaze, Arnaud D.; Santhanam, Prasanna; Erqou, Sebhat; Bertoni, Alain G.; Ahima, Rexford S.; Echouffo-Tcheugui, Justin B.
Abstract: Aim: To evaluate the associations of microvascular disease (MVD) with incident cardiovascular disease (CVD) in individuals with type 2 diabetes. Methods: A total of 4098 participants with type 2 diabetes and without CVD were assessed for MVD (diabetic kidney disease, retinopathy or neuropathy) in the Look AHEAD (Action for Health in Diabetes) study. Cox models were used to generate hazard ratios (HRs) for: (1) CVD composite (myocardial infarction, stroke, hospitalization for angina and/or death from cardiovascular causes), (2) coronary artery disease (CAD), (3) stroke, and (4) CVD-related deaths. Results: Of 4098 participants, 34.7% (n = 1424) had MVD at baseline. Over a median of 9.5 years, 487 developed the CVD composite, 410 CAD events, 100  stroke, and 54 CVD-related deaths. After adjusting for relevant confounders, MVD was associated with increased risks of CVD composite (HR 1.34, 95% CI 1.11–1.61), CAD (HR 1.24, 95% CI 1.01–1.52), stroke (HR 1.55, 95% CI 1.03–2.33), and cardiovascular mortality (HR 1.26, 95% CI 0.72–2.22). HRs for CVD composite by type of MVD were 1.11 (95% CI 0.89–1.38), 1.63 (95% CI 1.22–2.17) and 1.16 (95% CI 0.92–1.46) for diabetic kidney disease, retinopathy, and neuropathy, respectively. Conclusions: Our findings underscore the relevance of MVD in CVD risk assessment in type 2 diabetes.